Cultural Persistence in the Architecture of Sa’o Nggua: A Case Study of Traditional Lio Settlements in Nggela, Flores Island - Mukhlis A. Mukhtar; A Antariksa; Lisa Dwi Wulandari (Malikussaleh University, Aceh, Indonesia, 2025)
This study investigates the persistence of cultural meaning in the traditional architecture of Sa’o Nggua within the Nggela settlement of the Lio ethnic group in Flores, Indonesia. Through a structuralist and ethnographic approach, the research analyzes spatial patterns, architectural typologies, and ritual calendars at both macro (village) and micro (house-cluster) scales. Findings reveal that the settlement exhibits a sectoral-concentric spatial configuration aligned with cosmological beliefs, where sacred–profane binaries structure both space and function. Despite modern pressures and environmental disruptions, architectural forms remain consistent—particularly the tripartite interior and symbolic roof—due to ritual obligations and local material abundance. Twelve annual rites form an eco-ritual feedback loop, ensuring house maintenance and agricultural productivity. The coexistence of Catholic worship and ancestral practices demonstrates a layered cultural resilience. Limitations include a lack of spatial quantification and gendered labor metrics. Future research should explore UAV-based mapping, longitudinal ethnography, and climate-adaptive potentials of indigenous construction techniques. Overall, Sa’o Nggua functions not merely as a shelter but as a living symbol of cultural continuity, ecological adaptation, and social cohesion in the face of change. This underscores the relevance of vernacular architecture as a model for sustainable and resilient built environments.